"The Cure of Souls is the Art of Arts:" Preaching, Confession, and Catechesis in the Middle Ages. Issue 9 (4th September 2013) - Reeves, Andrew
Abstract: In the European Middle Ages, the area in which the majority of lay Christians came into contact with the so‐called institutional Church was pastoral care. Three principle areas of this care were preaching, confession, and catechesis. All three provide a window into popular religious practice, and thus, the study of pastoral care benefitted from the social‐historical turn of the 1960s and 1970s and an increased emphasis on "the people." One of the key aspects of this study of pastoral care has been in investigation of pastoralia, those works of literature meant to help clergy with the cure of souls carry out their tasks. The study of pastoralia begins with the manuscripts, but then aids several different approaches: history of sexuality, feminism, social and cultural history, and history of universities all make abundant use of pastoral literature.